ART-VERBAL CREATIVITY OF PUPILS: A DIALOGIC CONTEXT - Юрченко, З. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The author reveals the main psychological aspects of pupils’ literary self-expression and its dialogic context which actualizes one’s self-knowledge capabilities.